Five Pillar Experiences as an Alternative Approach to Sustainable Tourism: A Critical Review of Mass Tourism Practices in Bali Province - Natalia, Fika Risma; Wiranata, Anom (Universitas Padjadjaran, 2026)
Abstract This article examines the role of the tourism sector in Bali in its influence on social, cultural, and environmental sustainability, focusing on the impacts of mass tourism through the Five Pillar Experiences approach. The aim of this research is to analyze how a community empowermentbased tourism model can contribute to creating sustainable and equitable tourism. The method used is a qualitative approach with a case study, examined through the conceptual framework of sustainable tourism and community-based action. This research shows that mass tourism has led to the commodification of Balinese culture and environmental degradation. Therefore, the Five Pillar Experiences offer a solution by empowering local communities and promoting cultural and ecosystem sustainability. The suggestion made is the need to strengthen community-based tourism policies that actively involve local communities in every stage of decisionmaking, in order to ensure that the economic benefits of tourism can be enjoyed equitably without compromising the sustainability of Bali's culture and environment. Artikel ini mengkaji peran sektor pariwisata di Bali dalam pengaruhnya terhadap keberlanjutan sosial, budaya, dan lingkungan, dengan fokus pada dampak pariwisata massal melalui pendekatan Five Pillar Experiences. Tujuan penelitian ini adalah untuk menganalisis model pariwisata berbasis pemberdayaan masyarakat lokal dapat berkontribusi dalam menciptakan pariwisata yang berkelanjutan dan adil. Metode yang digunakan adalah pendekatan kualitatif dengan studi kasus, yang dikaji melalui kerangka konseptual sustainable tourism dan community based action. Penelitian ini menunjukkan bahwa pariwisata massal telah menyebabkan komodifikasi budaya Bali dan kerusakan lingkungan. Oleh karena itu, Five Pillar Experiences menawarkan solusi dengan memberdayakan komunitas lokal dan mempromosikan keberlanjutan budaya dan ekosistem. Saran yang diberikan adalah perlunya penguatan kebijakan pariwisata berbasis komunitas yang melibatkan masyarakat lokal secara aktif dalam setiap tahap pengambilan keputusan, guna memastikan bahwa keuntungan ekonomi dari pariwisata dapat dinikmati secara merata tanpa mengorbankan keberlanjutan budaya dan lingkungan Bali.